2021
DOI: 10.1177/08850666211028139
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status and Clinical Outcomes in Acute Respiratory Distress Syndrome: A Secondary Analysis From the Assessment of Low Tidal Volume and Elevated End-Expiratory Volume to Obviate Lung Injury (ALVEOLI) Trial

Abstract: Background: Acute respiratory distress syndrome (ARDS) is a highly morbid condition that has limited therapeutic options. Optimal vitamin D status has been linked to immunological effects that may benefit critically ill patients. Therefore, we investigated whether admission 25-hydroxyvitamin D levels (25OHD) are associated with clinical outcomes in ARDS patients. Methods: We performed a secondary analysis of data from a randomized, controlled trial comparing oxygenation strategies in 549 patients with ARDS (NC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…In 2022, a secondary analysis of the ALVEOLI study was carried out to explore the connection between vitamin D status and two outcomes: ventilator-free days and 90-day survival [89]. The study revealed that patients with vitamin D deficiency had a longer duration of mechanical ventilation and a greater likelihood of 90-day mortality.…”
Section: Vitamin Dmentioning
confidence: 99%
“…In 2022, a secondary analysis of the ALVEOLI study was carried out to explore the connection between vitamin D status and two outcomes: ventilator-free days and 90-day survival [89]. The study revealed that patients with vitamin D deficiency had a longer duration of mechanical ventilation and a greater likelihood of 90-day mortality.…”
Section: Vitamin Dmentioning
confidence: 99%
“…Vitamin D status was also associated with the duration of mechanical ventilation and mortality in patients admitted with ARDS. Data analysis of a randomized, controlled trial from the ALVEOLI study revealed that severe vitamin D deficiency was common in patients with ARDS [ 140 ]. In fact, patients with 25(OH)D3 < 10 ng/mL were likely to be ventilated for nine days longer than patients with levels >10 ng/mL and showed a higher risk of 90-day mortality [ 140 ].…”
Section: Vitamin D and Covid-19mentioning
confidence: 99%
“…The advantage of calcidiol administration was reported in osteoporotic patients [ 160 ]. Furthermore, the best route of administration and early treatment must be considered, taking into account the clinical characteristics of the patients, baseline 25(OH)D3 levels, and outcome measurement [ 140 , 161 ]. Although some studies considered serum 25(OH)D3 as a negative acute-phase reactant [ 162 ], nonetheless, supplementation with the hormone was found to be generally helpful in COVID-19 outcomes.…”
Section: Vitamin D Supplementation and Covid-19mentioning
confidence: 99%